2015
DOI: 10.1016/j.jvs.2013.11.099
|View full text |Cite
|
Sign up to set email alerts
|

Association between seven single nucleotide polymorphisms involved in inflammation and proteolysis and abdominal aortic aneurysm

Abstract: The SNPs included in this analysis were not associated with AAA presence in either study population. However, meta-analysis of the currently available data disclosed a positive association for MMP-3 rs3025058 and MTHFR rs1801133.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
36
2
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 29 publications
(40 citation statements)
references
References 51 publications
(83 reference statements)
1
36
2
1
Order By: Relevance
“…Further meta-analyses of gene-association studies have identified positive associations for the following SNPs: MMP-3 rs3025058,33 MMP-2 rs243865,34 MMP-13 rs2252070,34 elastin rs2071307,34 C reactive protein rs3091244,35TGF β rs764522 and rs1036095 36. A recent meta-analysis (in press) from our group has not confirmed previously identified putative associations for the ACE inhibitors rs3025058, MMP-3 rs3025058, nitric oxide synthase rs1799752 and methylenetetrahydrofolate reductase rs1801133 SNPs 37. Finally, Jones et al 38 analysed 44 blood lipid- and coronary artery disease-associated loci in a discovery cohort from New Zealand.…”
Section: Genetic Studiescontrasting
confidence: 53%
“…Further meta-analyses of gene-association studies have identified positive associations for the following SNPs: MMP-3 rs3025058,33 MMP-2 rs243865,34 MMP-13 rs2252070,34 elastin rs2071307,34 C reactive protein rs3091244,35TGF β rs764522 and rs1036095 36. A recent meta-analysis (in press) from our group has not confirmed previously identified putative associations for the ACE inhibitors rs3025058, MMP-3 rs3025058, nitric oxide synthase rs1799752 and methylenetetrahydrofolate reductase rs1801133 SNPs 37. Finally, Jones et al 38 analysed 44 blood lipid- and coronary artery disease-associated loci in a discovery cohort from New Zealand.…”
Section: Genetic Studiescontrasting
confidence: 53%
“…Another one, published the same year, which was investigated several genes in AAA presented the similar results for MMP-3 rs3025058 [116].…”
Section: Mmp-3mentioning
confidence: 56%
“…This was tried to be explained by studies on genes effecting the chemokine receptors with important role in the inflammatory process and on gene deletions that play a role in oxidative stress such as endothelial nitric oxide synthase (eNOS) and by many other pathogenetic studies (7). There are also more recent studies on the roles of inflammation and proteolytic process in the pathophysiology and epidemiology of AAA (21)(22)(23). AAA was found to be ten times more frequent in the first-degree relatives of patients with AAA.…”
Section: Discussionmentioning
confidence: 99%